Antianemia Drug Roxadustat (FG-4592) Protects Against Doxorubicin-Induced Cardiotoxicity by Targeting Antiapoptotic and Antioxidative Pathways - Long, Guangfeng; Chen, Hongbing; Wu, Mengying; Li, Yuanyuan; Gao, Ling; Huang, Songming; Zhang, Yue; Jia, Zhanjun; Xia, Weiwei (Frontiers in Pharmacology, 2020)
Abstract Doxorubicin (DOX) is broadly used in treating various malignant tumors. However, its cardiotoxicity limits its clinical use. Roxadustat (FG-4592) is a new hypoxia-inducible factor prolyl hydroxylase (HIF-PHD) inhibitor and has been approved for treating anemia in chronic kidney diseases (CKD) patients. However, the role of FG-4592 in DOX-induced cardiotoxicity remains unknown. In this study, Mouse cardiac function was evaluated by echocardiography, plasma LDH/CK-MB, and heart HE staining. Cell apoptosis, oxidative stress, inflammation, and HIF-target genes were evaluated in mouse cardiac tissue and rat cardiomyocyte cells (H9c2) exposed to DOX with FG-4592 pretreatment. DOX-sensitive HepG2 and MCF-7 cell lines were used to evaluate FG-4592 effect on the anticancer activity of DOX. We found that FG-4592 alleviated DOX-induced cardiotoxicity shown by the protection against cardiac dysfunction, cardiac apoptosis, and oxidative stress without the effect on inflammatory response. FG-4592 alone did not change the cardiac function, cardiomyocyte morphology, oxidative stress, and inflammation in vivo. FG-4592 could protect cardiomyocytes against DOX-induced apoptosis and ROS production in line with the upregulation of HIF-1α and its target genes of Bcl-2 and SOD2. Importantly, FG-4592 did not impact the anticancer activity of DOX. These findings highlighted the protective effect of FG-2 4592 on DOX-induced cardiotoxicity possibly through upregulating HIF-1α and its target genes antagonizing apoptosis and oxidative stress.